2021
DOI: 10.3390/metabo11120842
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Proteomics Dynamics of Serum Samples Reveals Dietary Zeolite Clinoptilolite Supplementation Restores Energy Balance in High Yielding Dairy Cows

Abstract: Dairy cows can suffer from a negative energy balance (NEB) during their transition from the dry period to early lactation, which can increase the risk of postpartum diseases such as clinical ketosis, mastitis, and fatty liver. Zeolite clinoptilolite (CPL), due to its ion-exchange property, has often been used to treat NEB in animals. However, limited information is available on the dynamics of global metabolomics and proteomic profiles in serum that could provide a better understanding of the associated altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
1
3
0
1
Order By: Relevance
“…From a technical standpoint, the mathematical difference indicates an improvement in the prevalence of ketosis development, which subsequently has implications on the reproductive health. Similar results were obtained by Maity et al. (2021) and Masoumi Pour et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From a technical standpoint, the mathematical difference indicates an improvement in the prevalence of ketosis development, which subsequently has implications on the reproductive health. Similar results were obtained by Maity et al. (2021) and Masoumi Pour et al.…”
Section: Discussionsupporting
confidence: 89%
“…Reversible ion exchange and adsorption capacity, related to the elimination of toxic agents, can be used to restore homeostasis and energy balance within an animal's body; for example, by eliminating the excessive production of ammonia and other gaseous products in rumen, including CO2 and H2S, which are due to unbalanced digestion or various pathologies ( Maity et al., 2021 ; Mastinu et al., 2019 ; Pavelić et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites are natural, microporous, three-dimensional crystalline materials with well-defined channels and cavities and various technological applications in veterinary medicine [ 176 , 177 ]. Moreover, a widely used zeolite is known as clinoptilolite, which has been proven as safe for veterinary use [ 178 ], acting as an antibacterial, antiviral, antioxidant, anti-diarrheic, and growth-promoting agent [ 165 , 166 , 178 , 179 ]. Đuričić et al [ 165 ], studying dietary vibroactivated and micronised clinoptilolite, found out its effect on reducing the incidence of intramammary infections, while Ural [ 180 ] reported the efficacy of supplementation with 3% clinoptilolite in dairy cows in terms of milk yield and somatic cell count.…”
Section: Alternative Strategies—potential Solutionsmentioning
confidence: 99%
“…Literatura Citada ecosistema ruminal, aumentando la producción de propionato en el rumen y la digestión post-ruminal del almidón, permitiendo mejorar el estado energético de los animales, disminuyendo los efectos adversos de la cetosis subclínica, y del estrés metabólico y oxidativo (Karatzia et al, 2013;Maity et al, 2021). Los efectos de la CLP, mencionados anteriormente, pueden haber fortalecido el sistema inmune de las vacas y explicaría la reducción del RCS, lo cual reduce el riesgo de contraer enfermedades intramamarias (Đuričić et al, 2017; Đuričić et al, 2020).…”
Section: Conclusiónunclassified